The First Total Synthesis of Pectinolide F - Sabitha, Gowravaram; Gurumurthy, Chevula; Yadav, Jhillu Singh (Synthesis, 2014)
The first total synthesis of the natural saturated α-pyrone pectinolide F has been accomplished from inexpensive, commercially available (S)-ethyl lactate and but-3-yn-1-ol. The salient features of the synthesis are 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO)–[bis(acetoxy)iodo]benzene oxidation, Sharpless asymmetric dihydroxylation, Grignard reaction, and partial hydrogenation of the triple bond.
Keywords: pectinolide F; δ-lactones; Grignard reaction; Lindlar’s catalyst; total synthesis